Gangs on the Street, Gangs in Prison: Their Nature, Interrelationship, Control, and Re-Entry, Texas, 2016-2018 - Decker, Scott H. ([Verlag nicht ermittelbar], 2021)
This study includes 802 interviews that were conducted in two Texas prisons with inmates who were within a week of release. 532 of these individuals were re-interviewed within roughly one month of their release and 482 were re-interviewed roughly nine months after release. In addition to interviews, Texas Department of Criminal Justice Records were made available to the research team and half of the interviews were conducted with identified gang members. This study assesses whether gang members can be surveyed in prisons with fidelity and reports descriptive statistics on gang and non-gang members. More than forty separate scales were included in the interview.